5x+7+2=12+3-3x

Simple and best practice solution for 5x+7+2=12+3-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+7+2=12+3-3x equation:


Simplifying
5x + 7 + 2 = 12 + 3 + -3x

Reorder the terms:
7 + 2 + 5x = 12 + 3 + -3x

Combine like terms: 7 + 2 = 9
9 + 5x = 12 + 3 + -3x

Combine like terms: 12 + 3 = 15
9 + 5x = 15 + -3x

Solving
9 + 5x = 15 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
9 + 5x + 3x = 15 + -3x + 3x

Combine like terms: 5x + 3x = 8x
9 + 8x = 15 + -3x + 3x

Combine like terms: -3x + 3x = 0
9 + 8x = 15 + 0
9 + 8x = 15

Add '-9' to each side of the equation.
9 + -9 + 8x = 15 + -9

Combine like terms: 9 + -9 = 0
0 + 8x = 15 + -9
8x = 15 + -9

Combine like terms: 15 + -9 = 6
8x = 6

Divide each side by '8'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| 8x-1=9x-2 | | -3y+37=-2(y-6) | | 25p^2-16= | | x/26.75=35.67 | | 3s+10=5s+3 | | y=-6+34 | | 13x+7=16x-4 | | -2(w+8)=-5w-43 | | y=8x-128 | | 26.75*x=35.67 | | b-3/5=-1 | | 4x-8+6x+9= | | 0=16t^2+120t | | 3(3x+4)=21 | | 6(x+9)=3(8+3x) | | 2/3p=10 | | 120=50 | | 3x=-14x | | 7a+84=7 | | 22x+6-24x=5-9 | | 3(y+5)+5y=7 | | -14r-6r-7r+-13=2 | | xsquared=324 | | 8=-4x+8(x-2) | | 3v^2-19v-40=0 | | 111-3x^2=0 | | 8+7x=4x+41 | | 20y-9y-4y+2y-8y=19 | | 2(2x-7)=7 | | 6x-5=7x+3 | | 119=7x-4(-4x+22) | | 2(v+2)-6v=24 |

Equations solver categories